The Relationship of Behavior Factors with Helminthiasis Incident on Helminthiasis Infection Disease in Pregnant Mothers in Langkat Regency - Rini Aswita; Fazidah Aguslina Siregar; Nurmaini (Britain International for Academic Research (BIAR) Publisher, 2020)
The aim of the study is to find out the behavior factors helminthiasis Infection Disease in Pregnant Mothers. The sample size in this study was determined based on the sample size formula for testing the hypothesis of the proportion of one clinical study population of Skovland and Vatn (2007). The results of research on the influence of behavioral factors and environmental factors on helminthiasis in pregnant women in Langkat Regency in 2019 are Helminthiasis status. There are 175 pregnant women, 20 percent of pregnant women are infected with helminthiasis, and the most common type of worm is Ascaris lumbricoides. Behavioral factors. Behavioral factors have a significant influence on the incidence of helminthiasis in pregnant women, namely the habit of wearing footwear, the habit of washing hands with soap before eating and after defecation, the habit of consuming raw food and the habit of defecating in addition to toilet.